2022
DOI: 10.3390/jcm11061661
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Assessment of Angiographies at Different Depths with AS-OCTA: Implication for Functions of Post-Trabeculectomy Filtering Bleb

Abstract: This study aimed to analyze the quantitative vascular biomarkers of filtering bleb function at different depths using anterior segment optical coherence tomography angiography (AS-OCTA). This cross-sectional study is registered on Clinicaltrails.gov (NCT 04515017). Forty-six eyes with primary open-angle glaucoma that had undergone trabeculectomy with mitomycin-C for more than six months were included. Vessel density (VD) and vessel diameter index (VDI) in the superficial layer (SL), Tenon’s layer (TL), and dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The previous study showed a better correlation between VD and postoperative IOP results than that obtained with the IBAGS and MBGS. 28 The slit-lamp classifications were subjective, and their AUC was relatively unsatisfactory. MVMS-BH-MCS presented by the Loess plot, a value of 17.61 was used as an early warning biomarker of the functional change of the filtering blebs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study showed a better correlation between VD and postoperative IOP results than that obtained with the IBAGS and MBGS. 28 The slit-lamp classifications were subjective, and their AUC was relatively unsatisfactory. MVMS-BH-MCS presented by the Loess plot, a value of 17.61 was used as an early warning biomarker of the functional change of the filtering blebs.…”
Section: Discussionmentioning
confidence: 99%
“…), as previously described. 28 Briefly, the operator made a rectangular scleral flap at the size of 3 × 4 mm, and the cotton containing MMC was put for 2 minutes (Hanhui Pharmaceuticals Co., Ltd, China; 10 mg/vial). A piece of trabecular meshwork was removed, and a peripheral iridectomy was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations